PENUTUPAN KARANG DI PULAU BARANGLOMPO DAN PULAU BONE BATANG BERDASARKAN METODE REEF CHECK - Ilham, Ilham; Litaay, Magdalena; Priosambodo, Dody; Moka, Willem (Jurnal Ilmu Kelautan SPERMONDE, 2017)
The Research on “Coral Coverage in Baranglompo Island and Bone Batang Island Based on Reef Check Method” was conductedin April 2016. The aims of this study was to determine and to compare the condition of reefs in Baranglompo and Bone BatangIslands based on the percentage of life coral cover by using Reef Check methods. This study also aims to determine whichfactors that most affect the percentage of coral cover on each island i.e: abiotic factors (temperature, salinity and substrate inthe form of rock, rubble, sand, silt/clay); biotic factors (soft coral, recent killed coral, algae, sponges, fish and invertebratesassociate) and anthropogenic factors (garbage, ilegal fishing/bombs, stun, anchors, nets) were also investigated. Percentage oflife coral cover obtained by Line Intercept Transect (LIT) along 100 meters at a depth of 3 meters and 10 meters. The resultsshowed that the condition of coral reefs in Baranglompo was classified as moderate with an average percentage coral coverageof 42% at a depth of 3 meters and 27% at a depth of 10 meters. While the condition of coral reefs in Pulau Bone Batang wasrelatively good with average coral cover of 51% at 3 meters depth and moderate with average coral cover of 39% at 10 metersdepth. Condition of coral reefs in Bone Batang is better than Baranglompo islands. Anthropogenic impacts in the form of wasteis the most influential factor on coral cover on the island Baranglompo. Whereas fishing activities by using dinamite are thefactors that most influence on coral cover on the island of Bone Batang.Keywords: Coral coverage, Baranglompo island, Bone Batang island, Reef Check